2018
DOI: 10.1002/crat.201700257
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Temperature Induced (020) Growth Facets of Nebulizer Sprayed BiVO4 Thin Films for Effective Photodegradation of Rhodamine B

Abstract: The high-efficient and visible-light active monoclinic BiVO 4 thin films with preferentially oriented (020) facets are successfully deposited by nebulizer spray pyrolysis technique. The role of substrate temperature over crystal growth facets and other physical properties of BiVO 4 films are analyzed using XRD, HRTEM, UV spectrometer, and Raman analysis. The BiVO 4 thin film deposited at 350°C possesses broad absorbance in the visible region with highly exposed (020) facet is obtained. Room temperature photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Hence, the efficient adsorption of reactant molecules on the surface facilitates the enhancement of photocatalytic activity. For instance, Ravidhas et al reported the highly oriented {040} facet had a relatively high specific surface area and a larger atom density to adsorb more dye molecules on the surface of m BiVO 4 , resulting in an enhanced photocatalytic performance for RhB degradation . Thalluri et al reported that the highly exposed {040} facet increased the O–H species that directly participated in the adsorption of ethylene on the surface of m BiVO 4 catalyst as well as the generation of hydroxyl radicals, thereby significantly improving the photocatalytic performance …”
Section: Facet Engineering On the Surfcae Of Mbivo4mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the efficient adsorption of reactant molecules on the surface facilitates the enhancement of photocatalytic activity. For instance, Ravidhas et al reported the highly oriented {040} facet had a relatively high specific surface area and a larger atom density to adsorb more dye molecules on the surface of m BiVO 4 , resulting in an enhanced photocatalytic performance for RhB degradation . Thalluri et al reported that the highly exposed {040} facet increased the O–H species that directly participated in the adsorption of ethylene on the surface of m BiVO 4 catalyst as well as the generation of hydroxyl radicals, thereby significantly improving the photocatalytic performance …”
Section: Facet Engineering On the Surfcae Of Mbivo4mentioning
confidence: 99%
“…For instance, Ravidhas et al reported the highly oriented {040} facet had a relatively high specific surface area and a larger atom density to adsorb more dye molecules on the surface of mBiVO 4 , resulting in an enhanced photocatalytic performance for RhB degradation. 97 Thalluri et al reported that the highly exposed {040} facet increased the O−H species that directly participated in the adsorption of ethylene on the surface of mBiVO 4 catalyst as well as the generation of hydroxyl radicals, thereby significantly improving the photocatalytic performance. 76 In addition to the difference in molecular adsorption associated with surface facets, the separation and transfer of photogenerated charge carriers is also related to the physicochemical properties and surface states of the faceted semiconductors, which is another factor that can affect the photocatalytic activity.…”
Section: Facet Engineering On the Surfcae Of Mbivomentioning
confidence: 99%
“…[32] In this context, modified spray coater with jet-nebulizer nozzle will overcome the particle clogging issue at nozzle. Unlike conventional spray coating nozzle, the nebulizer will form cloud type aerosol facilitate uniform coating on the substrate [33][34][35][36]. This may anticipate to produce homogenous and highly reactive CZTS catalyst film.…”
Section: Introductionmentioning
confidence: 99%